Reflectance confocal microscopy: a useful and non-invasive tool in the in vivo differentiation of benign pigmented skin lesions from malignant melanoma. Report of a case - Mofarrah, Ramin; Ahlgrimm-Seiss, Verena; Massone, Cesare; Hofmann-Wellenhof, Rainer (Dermatology Practical & Conceptual, 2013)
The diagnosis of seborrheic keratoses (SK) undergoing regression can be challenging clinically and dermoscopically. We report a case of a SK with a history of change and equivocal dermoscopic features, thereby showing confocal features suggestive of solar lentigo/early SK. The present case emphasizes the potential value of reflectance confocal microscopy (RCM) in the differentiation of malignant from benign pigmented skin lesions.